Gastrointestinal Infantile Hemangioma: Presentation and Management. Issue 4 (October 2015) - Soukoulis, Ines W.; Liang, Marilyn G.; Fox, Victor L.; Mulliken, John B.; Alomari, Ahmad I.; Fishman, Steven J.
ABSTRACT: Objectives: The aim of the present study was to document the clinical presentation, diagnostic studies, and therapy of gastrointestinal infantile hemangiomas. Methods: This is a retrospective analysis of children with gastrointestinal hemangiomas culled from our Vascular Anomalies Center database. We detailed the location of visceral and cutaneous tumors, as well as radiologic and procedural methods used for diagnosis and treatment. Results: A total of 9 of the 16 children (14 girls and 2 boys) with hollow visceral hemangiomas also had cutaneous lesions. The most common extravisceral sites were regional facial lesions (n = 6), multifocal lesions (n = 2), and a solitary chest lesion (n = 1). Presenting symptoms were melena and hematochezia in the first 4 months of life (n = 14); several infants required multiple blood transfusions. The most frequent locations were small bowel and mesentery. One-half of the patients (n = 8) were diagnosed by laparotomy; the majority (n = 12) had suspicious radiologic findings. Corticosteroid and/or propranolol were the most common therapies. Conclusions: Melena and hematochezia, sometimes with profound anemia, in the first 4 months of life, suggest the possibility of intestinal infantile hemangioma even in the absence of cutaneous tumor. Intestinal bleeding, particularly in association with a regional facial lesion, should initiate workup: ultrasonography, computed tomography, and magnetic resonance imaging display diagnostic features. First-line treatment is medical management; bowel resection may be necessary, particularly for perforation.